Hidroquímica do aquifero aluvionar do baixo Jaguaribe Itaiçaba-Ceará - Nobre, Maria Elisangela da Silva (2014)
In upstate of Ceará, groundwater is considered precious sources of water supply, and the main sources of water exploration in sedimentary and alluvial areas. The research was conducted in the village of Itaiçaba, inserted in the Baixo Jaguaribe Hydrographic Basin, where the population, though, resourced CAGECE uses the abstraction of groundwater for its water supply, mainly in subsistence agriculture and livestock. The region has extensive areas of shrimp farming, which can cause problems to the environment, such as eutrophication, structural changes in biological communities and heavy metal contamination. The main objectives of this research were to provide analyzes: bacteriological, major and minor elements, the first data on trace metals (Al, Ba, Cr, Ni, Mn and Pb) in the municipality, the O18 isotopes, fluid balance and vulnerability. The methodology consisted of 21 samples collected in three campaigns, including periods of drought and rain, between the years 2012 and 2013. The techniques used correspond to potentiometric methods, spectrophotometric, titrimetric, atomic absorption spectrometry and plate count basically referenced by Standard Methods and classified according to the standards nº 357/05 CONAMA Resolution and Ordinance nº 2914/11, the Ministry of Health. According to analytical interpretation, coliform bacteria were detected in the second and third sampling; The pH of the samples were between 6.1 to 8.5, except for P9 (pH = 3.9), whose acidity contributed to high levels of aluminum at this point; conductivity ranged between 307 and 5940 µS/cm; the waters are classified as Sodic Chlorinated; are above the standard of potability the following contents: chloride in 33% of samples; STD, <62%; turbidity, 70%; nitrate, an average of 33%; and iron, 19%. It was found the presence of aluminum, barium, lead, manganese and nickel in samples. According to O18 in the river there is a marked influence of evaporation, including the shrimp farming tanks and some wells capture water of deep aquifer, and others mix between aquifer, river and rain did not follow the seasonal variation. The water balance was positive for months of high rainfall, keeping the water deficit for the other months of the year; Aquifer was classified as medium to high vulnerability to contamination, by the methodology GOD; It was concluded that most of the wells continues to showing traces of human intervention, including the shrimp farming, being inappropriate for its potability risk of harm the organism.